Three-Dimensional Printing Applications in Food Industry - Areti Leontiou; Stavros Georgopoulos; Vassilios K. Karabagias; George Kehayias; Anastasios Karakassides; Constantinos E. Salmas; Aris E. Giannakas (Nanomanufacturing, 2023)
Three-dimensional (3D) printing has gained increasing attention for its unique ability to create geometrically complex designs, which not only can be used for mass manufacturing but also has environmental and economic benefits. Additionally, as far as the food industry is concerned, this emerging technology has the potential to personalize products in terms of shape and/or nutritional requirements creating a wide range of food items with specially made shapes, colors, textures, tastes, and even nutrition using suitable raw materials/food components. In the future, 3D food printing could make complex food models with special interior design. This review gives attention to intelligent food packaging. Point-of-use machinery for manufacturing smart packaging, with a 3D printing approach, enables the use of multifunctional smart components and is self-identifying and highly sensitive, while using biocompatible non-toxic materials is cheaper than traditional manufacturing methods. This would create smart food packaging and in turn prevent customers from purchasing unsuitable food and thus reduce food waste. Future studies can make the process more compatible and efficient with a wide variety of materials that could be used to improve the 3D printing process.